2006
DOI: 10.1002/eji.200636173
|View full text |Cite
|
Sign up to set email alerts
|

An important role of Tyk2 in APC function of dendritic cells for priming CD8+ T cells producing IFN‐γ

Abstract: Tyrosine kinase 2 (Tyk2) contributes to the signals triggered by IL-12 for IFN-c production by NK cells and T cells. We found in this study that Tyk2-deficient (-/-) mice showed increased susceptibility at the early stage after an i.p. infection with Listeria monocytogenes, accompanied by impaired IFN-c production. The numbers of both MHC class Ib (H2-M3)-or MHC class Ia (K b )-restricted CD8 + T cells producing IFN-c and exhibiting cytotoxicity were significantly decreased in Tyk2 -/-mice after infection with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 30 publications
(39 reference statements)
1
20
1
Order By: Relevance
“…4B), indicating that the impaired IFN-g production of KO CD4 T cells was not due to a decreased bacterial burden. The difference in bacterial number between WT and Tyk2 KO mice was smaller compared with our previous study (27), possibly because of the altered bacterial virulence and different number of inoculated bacteria. By examining IFN-g production of various cell subsets at day 2 postinfection, it was revealed that the majority of IFN-g-producing cells were NK cells, which were reduced in Tyk2 KO mice (Fig.…”
Section: Tyk2-dependent Bystander Ifn-g Production From Naturally Occcontrasting
confidence: 77%
See 1 more Smart Citation
“…4B), indicating that the impaired IFN-g production of KO CD4 T cells was not due to a decreased bacterial burden. The difference in bacterial number between WT and Tyk2 KO mice was smaller compared with our previous study (27), possibly because of the altered bacterial virulence and different number of inoculated bacteria. By examining IFN-g production of various cell subsets at day 2 postinfection, it was revealed that the majority of IFN-g-producing cells were NK cells, which were reduced in Tyk2 KO mice (Fig.…”
Section: Tyk2-dependent Bystander Ifn-g Production From Naturally Occcontrasting
confidence: 77%
“…Tyk2-deficient mice showed an impaired early protection against L. monocytogenes infection (27). Although Tyk2-dependent IFN-g production by NK cells, NK-T cells, MP CD8 T cells, as well as TCR gd T cells might be involved in the early protection against listerial infection, earlier results also suggest a role of Th1 cells.…”
Section: Tyk2-dependent Bystander Ifn-g Production From Naturally Occmentioning
confidence: 92%
“…have failed to show any defects in Tyk2 À/À DC maturation and their ability to stimulate T-cell proliferation in vitro (15). Nevertheless, we cannot yet fully exclude a contribution of Tyk2 for DC functions in vivo.…”
Section: Discussionmentioning
confidence: 80%
“…Mice deficient for Tyk2 (Tyk2 À/À mice) are viable and fertile but were described to have defects in type I IFN, IL12, and also type II IFN (IFNg) signaling (11,12). Tyk2 À/À mice show an increased susceptibility to various pathogens (11,(13)(14)(15) but are resistant against lipopolysaccharide (LPS)-induced endotoxin shock (16). In addition, Tyk2 is a key regulator for Th1/Th2 balance (17).…”
Section: Introductionmentioning
confidence: 99%
“…41 Moreover, it has recently been shown that Tyk2 Ϫ/Ϫ mice exhibit increased susceptibility to an infection with Listeria monocytogenes. 42 In humans, a hyper-IgE syndrome patient who lacks Tyk2 also shows unusual susceptibility to various microorganisms including viruses, fungi, and mycobacteria. 37 These results indicate that Tyk2 plays a nonredundant role in the protective immune responses against pathogens in both mice and humans.…”
Section: Discussionmentioning
confidence: 99%